Anti irradiation nanoparticles shelter immune organ from radio-damage via preventing the IKK/IκB/NF-κB activation - Shigao Huang; Min Xu; Xiaojun Deng; Qingyue Da; Miaomiao Li; Hao Huang; Lina Zhao; Linlin Jing; Haibo Wang (Molecular Cancer)
Abstract Background Normal tissue and immune organ protection are critical parts of the tumor radiation therapy process. Radiation-induced immune organ damage (RIOD) causes several side reactions by increasing oxidative stress and inflammatory responses, resulting in unsatisfactory curability in tumor radiation therapy. The aim of this study was to develop a novel and efficient anti irradiation nanoparticle and explore its mechanism of protecting splenic tissue from radiation in mice. Methods Nanoparticles of triphenylphosphine cation NIT radicals (NPs-TPP-NIT) were prepared and used to protect the spleens of mice irradiated with X-rays. Splenic tissue histopathology and hematological parameters were investigated to evaluate the protective effect of NPs-TPP-NIT against X-ray radiation. Proteomics was used to identify differentially expressed proteins related to inflammatory factor regulation. In addition, in vitro and in vivo experiments were performed to assess the impact of NPs-TPP-NIT on radiation therapy. Results NPs-TPP-NIT increased superoxide dismutase, catalase, and glutathione peroxidase activity and decreased malondialdehyde levels and reactive oxygen species generation in the spleens of mice after exposure to 6.0 Gy X-ray radiation. Moreover, NPs-TPP-NIT inhibited cell apoptosis, blocked the activation of cleaved cysteine aspartic acid–specific protease/proteinase, upregulated the expression of Bcl-2, and downregulated that of Bax. We confirmed that NPs-TPP-NIT prevented the IKK/IκB/NF-κB activation induced by ionizing radiation, thereby alleviating radiation-induced splenic inflammatory damage. In addition, when used during radiotherapy for tumors in mice, NPs-TPP-NIT exhibited no significant toxicity and conferred no significant tumor protective effects. Conclusions NPs-TPP-NIT prevented activation of IKK/IκB/NF-κB signaling, reduced secretion of pro-inflammatory factors, and promoted production of anti-inflammatory factors in the spleen, which exhibited radiation-induced damage repair capability without diminishing the therapeutic effect of radiation therapy. It suggests that NPs-TPP-NIT serve as a potential radioprotective drug to shelter immune organs from radiation-induced damage.